Merluccius tasmanicus Matallanas & Lloris 2006 is a junior synonym of M. australis (Hutton 1872) (Gadiformes: Merluciidae) based on morphological and molecular data - Antoni, Mariana Y. Deli; Delpiani, Sergio M.; Stewart, Andrew L.; González-Castro, Mariano; Astarloa, Juan M. Díaz De (Zootaxa, 2015)
The high intraspecific variation among and the conservative external morphology of Merluccius spp. have resulted in serious identification difficulties. Four hundred and twenty fresh and preserved specimens of Merluccius were analyzed, including the type series of Merluccius australis, M. tasmanicus and M. hubbsi; specimens of M. hubbsi from Argentina, Brazil and Uruguay, and individuals of M. australis from Argentina and New Zealand were examined. The nomenclatural status of the type specimens of M. australis is discussed and the designation of a lectotype and a paralectotype is proposed. The comparative study of morphology, meristic, traditional and landmark-based morphometry, both external and internal, and through DNA-based Barcoding molecular tools demonstrates that Merluccius tasmanicus is a junior synonym of Merluccius australis. Meristic and morphometric characters of types of M. tasmanicus completely overlap those of M. australis, whereas M. hubbsi show fewer scales along the lateral line, total vertebrae, second dorsal and anal-fin rays. A trend of a longer snout and wider head in M. australis and M. tasmanicus, and larger eyes and longer pelvic fins, in M. hubbsi was observed. While discriminant characters were found in the internal elements (hyomandibula, urohyal and sagitta otolith) between M. hubbsi and M. australis, none were observed between M. australis and those reported for M. tasmanicus. DNA barcoding analyses found no evidence of the existence of other species of Merluccius besides M. hubbsi and M. australis.